A case of generalized eosinophilic pustular folliculitis: treatment with JAK inhibitor - Chunzhi Zheng; Yueqian Yu; Guizhi Zhou; Hong Liu (Taylor & Francis Group, 2024)
AbstractAim This case study aims to report the efficacy and safety of a Janus kinase (JAK) inhibitor in the treatment of generalized eosinophilic pustular folliculitis (EPF).Methods We present a case of a 16-year-old Chinese patient who had been suffering from EPF for two years and had shown no response to both topical and systemic glucocorticoids. The patient was subsequently treated with oral tofacitinib at a dosage of 5mg daily.Results Significant remission of eruption and pruritus was observed in the patient upon treatment with tofacitinib. However, a relapse occurred upon dose reduction. Subsequent switch to the highly selective JAK1 inhibitor upadacitinib resulted in complete recovery, with the patient achieving a symptom-free status after six months.Conclusions JAK inhibitors show promise as a potential treatment option for EPF patients who do not respond to traditional therapies.